2006
DOI: 10.1016/j.jvs.2006.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from axillofemoral to in situ prosthetic reconstruction for the treatment of aortic graft infections at a single center

Abstract: ISR is a safe and effective alternative in the treatment of select patients with aortic graft infection. Graft reinfection occurred in 11.5% of the patients. The graft patency and limb salvages rates are excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
132
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 21 publications
3
132
1
5
Order By: Relevance
“…Несомненным пре-имуществом импрегнированных серебром протезов явля-ется их готовность к использованию сразу после вскрытия упаковки (нет необходимости замачивания в растворе антибиотика или антисептика), аналогичные неимпрег-нированным графтам плотность, прочность, отсутствие выраженной тканевой реакции и в первую очередь анти-микробные качества [21,[23][24][25]. Ряд исследователей [26][27][28][29][30][31] считают возможным использовать их даже в ин-фекционном очаге в позиции in situ, указывая на результа-ты, схожие с использованием алло-или аутовенозных графтов. Основным аргументом скептически настроенных ис-следователей становится отсутствие таких данных о нали-чии и выраженности антибактериальной активности этих протезов, которые бы не вызывали сомнений в своей до-стоверности.…”
Section: Discussionunclassified
“…Несомненным пре-имуществом импрегнированных серебром протезов явля-ется их готовность к использованию сразу после вскрытия упаковки (нет необходимости замачивания в растворе антибиотика или антисептика), аналогичные неимпрег-нированным графтам плотность, прочность, отсутствие выраженной тканевой реакции и в первую очередь анти-микробные качества [21,[23][24][25]. Ряд исследователей [26][27][28][29][30][31] считают возможным использовать их даже в ин-фекционном очаге в позиции in situ, указывая на результа-ты, схожие с использованием алло-или аутовенозных графтов. Основным аргументом скептически настроенных ис-следователей становится отсутствие таких данных о нали-чии и выраженности антибактериальной активности этих протезов, которые бы не вызывали сомнений в своей до-стоверности.…”
Section: Discussionunclassified
“…Antibiotic-soaked polyester prosthetic graft is an alternate conduit which can be used for in situ aortic reconstruction. Despite the benefits of expedient restoration of in-line flow to the lower extremities, reinfection rates exceed 10% [5][6][7]. Autogenous deep femoral and saphenous veins for the creation of a neoaortoiliac system (NAIS) have been used, Beck et al [8] reported a 5-year primary patency rate of 82% and and Ali et al [9] reported a cumulative primary patency at 72 months of 81% and limb salvage was 89%, with a five-year survival of 52%.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Since these surgical results were unsatisfactory, in situ vascular reconstruction has been used in recent years. [8][9][10] Using in situ vascular reconstruction, excellent longterm graft patency is expected, and blood flow to the lower limb is adequately maintained. Since there is no aortic stump, there is no risk of aortic stump disruption.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Bleeding due to aortic disruption or aortic/graft infection leads to sepsis, and the mortality rate early after operation has been reported to be 18%-54%. [2][3][4][5][6][7][8][9][10][11][12][13] Vascular reconstruction after removal of the infected graft had been the conventional method of surgery for sAEFs, and is performed by extra-anatomical bypass grafting. [1][2][3][4][5] However, extra-anatomical bypass grafting is associated with high rates of postoperative aortic stump re-infection or disruption, lower limb amputation, and death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation